AESTHETIC, TECHNOLOGICAL, AND SOCIAL IMPLICATIONS IN CONTEMPORARY FACIAL SURGERY: A SCOPING REVIEW PROTOCOL - Carneiro de Resende, Tatiana; Dib Rayashi, Abel; Pereira Silva, Éder; Pereira Arantes Almeida, Thalita (Revista Gênero e Interdisciplinaridade, 2026)
Introduction: Structured rhinoplasty stands out as an approach that integrates aesthetic and functional objectives, promoting lasting anatomical stability. With the increasing sophistication of techniques, it becomes essential to map recent technical advances in the field. Objective: To map and describe the available scientific evidence on trends and technical advances in structured rhinoplasty, also considering its aesthetic, functional, and sociocultural implications in the contemporary context of facial surgery. Method: A scoping review protocol was developed according to the Joanna Briggs Institute (JBI) guidelines and reported according to the PRISMA-ScR checklist. The review question was formulated based on the mnemonic PCC: Population - patients undergoing structured rhinoplasty; Concept - surgical techniques and technical innovations; Context - aesthetic and/or functional procedures. The searches will be conducted in six databases (PubMed, SciELO, Scopus, Web of Science, Embase, and Google Scholar), with studies published between 2015 and 2025, in Portuguese, English, or Spanish. Screening will be performed by two independent reviewers, extracting clinical and technical data, and conducting descriptive analysis with thematic categorization. Results: The aim is to identify the most recent approaches, such as the use of grafts (e.g., spreader graft, alar batten graft, septal extension graft), anatomical preservation, and technologies such as 3D imaging and preoperative simulation. The data will be presented in descriptive charts and tables. Discussion: The review should allow the identification of emerging surgical trends, gaps in the literature, and clinical patterns that support both the practice and teaching of structured rhinoplasty. Critical analysis of the data found will be compared with current literature to validate advances and technical innovations. Conclusion: The synthesis of these findings will contribute to the systematization of technical knowledge on structured rhinoplasty, providing support for safer and more effective clinical practices, as well as guiding future scientific investigations.